Pengaruh Komposisi Media Semai Sistem Tertutup Terhadap Perkecambahan Padi (Oryza Sativa L.) Inpari 32 - Harun, M Umar; Agustina, Heni; Bela, Triwulan Maryanita; Sopiana, Rina (Jurnal Agroekoteknologi, 2023)
One of the efforts to facilitate the way of taking rice seeds from the nursery media is to use plastic sacks instead of  directly from the soil.  To obtain the best planting media, experiments have been carried out on the no tidal swamp Rice   Fields, Pemulutan Village (3°05'42.7"S, 104°44'01.7"E), Ogan Ilir Regency, South Sumatra Province from June to August 2022.  The design method used was a Randomized Block Design. The treatments tested were four compositions of planting media mixtures, namely a mixture of soil with chicken manure, a mixture of black sand and chicken manure, a mixture of white sand and chicken manure, and black sand. The media composition ratio was 1:1 (V/V). All treatments were replicated three times to obtain 12 units. The seeds used are rice seeds of the Inpari 32 variety. The size of the seeding media made from plastic sacks was 160 cm x 100 cm, and the thickness of the entire planting media composition was 3 cm.  The plastic sacks used had a length of 180 cm and a width of 112 cm, and were used as a pad for a rice nursery which were 160 cm x 100 cm, and the thickness of all media compositions was 3 cm. The composition of the four treatments prior to the study showed that the pH was relatively the same (6.9-7.0) and the EC valuesvaried greatly (207-7734 mS), and at 14 day after plant (DAP) there was a decrease in pH to 4.3-5.3 and EC decreased drastically with narrow variations being (170-384 dS/cm).  Changes in the chemical properties of the media certainly had an impact on seed germination (70-90%) at 14 DAP of each media, and it turned out that the composiion of the type of planting media had  significant effect on sprout height, number of leaves, leaf length and sprout root length. In general, it can be concluded that the best media composition for rice germination is soil and chicken manure.